Expression of FAP, ADAM12, WISP1, and SOX11 is heterogeneous in aggressive fibromatosis and spatially relates to the histologic features of tumor activity. (26th November 2013) - Misemer, Benjamin S.; Skubitz, Amy P. N.; Carlos Manivel, J.; Schmechel, Stephen C.; Cheng, Edward Y.; Henriksen, Jonathan C.; Koopmeiners, Joseph S.; Corless, Christopher L.; Skubitz, Keith M.
Abstract: Aggressive fibromatosis (AF) represents a group of tumors with a variable and unpredictable clinical course, characterized by a monoclonal proliferation of myofibroblastic cells. The optimal treatment for AF remains unclear. Identification and validation of genes whose expression patterns are associated with AF may elucidate biological mechanisms in AF, and aid treatment selection. This study was designed to examine the protein expression by immunohistochemistry (IHC) of four genes, ADAM12, FAP, SOX11, and WISP1, that were found in an earlier study to be uniquely overexpressed in AF compared with normal tissues. Digital image analysis was performed to evaluate inter‐ and intratumor heterogeneity, and correlate protein expression with histologic features, including a histopathologic assessment of tumor activity, defined by nuclear chromatin density ratio (CDR). AF tumors exhibited marked inter‐ and intratumor histologic heterogeneity. Pathologic assessment of tumor activity and digital assessment of average nuclear size and CDR were all significantly correlated. IHC revealed protein expression of all four genes. IHC staining for ADAM12, FAP, and WISP1 correlated with CDR and was higher, whereas SOX11 staining was lower in tumors with earlier recurrence following excision. All four proteins were expressed, and the regional variation in tumor activity within and among AF cases was demonstrated. A spatial correlation between protein expression and nuclear morphology was observed. IHC also correlated with the probability of recurrence following excision. These proteins may be involved in AF pathogenesis and the corresponding pathways could serve as potential targets of therapy. Abstract : Immunohistochemistry and digital image analysis showed that the expression of ADAM12, FAP, WISP1, and SOX11 were markedly heterogeneous between and within aggressive fibromatosis (AF) cases, with higher expression in tumor areas in which cells had more "active" appearing nuclear features, suggesting that the corresponding pathways could serve as potential targets of therapy. High levels of protein expression of ADAM12, FAP, and WISP1, and low expression of SOX11, were associated with worse clinical outcome, defined by early (≤1 year) recurrence after excision versus nonrecurrence at ≥5 years.